Crystal Engineering of Phenylenebis(azanetriyl))tetrabenzoate Based Metal-Organic Frameworks for Gas Storage Applications - Mueller, Philipp; Bon, Volodymyr; Senkovska, Irena; Getzschmann, Juergen; Weiss, Manfred S.; Kaskel, Stefan (Crystal Growth and Design, 2017)
The metal-organic framework (MOF) Cu4(mpbatb)2 (mpbatb-4,4′,4″,4-(1,3-phenylenebis(azanetriyl))tetrabenzoate), also known as DUT-71 (DUT - Dresden University of Technology), was functionalized via postsynthetic cross-linking of the copper paddle wheels by linear salen derivatives and dabco (1,4-diazabicyclo[2.2.2]octane). This results in a series of porous MOFs, denoted as DUT-117(M) (M - Cu, Ni, Pd). Besides significant improvement of the framework robustness, the influence of the metal coordinated by the salen ligand on the gas adsorption capacity (hydrogen -196 °C, methane 25 °C, and carbon dioxide 25 °C) was investigated. In this series DUT-117(Ni) stands out as the best material for adsorptive methane storage with a high working capacity of 171 cm3·cm-3 between 5 and 65 bar.
CRIS-Team Scopus Importer:2022-04-14